2008
DOI: 10.1002/art.24073
|View full text |Cite
|
Sign up to set email alerts
|

Cited2 modulates hypoxia‐inducible factor–dependent expression of vascular endothelial growth factor in nucleus pulposus cells of the rat intervertebral disc

Abstract: Objective. To determine whether nucleus pulposus cells of the intervertebral disc express hypoxiainducible factor 2␣ (HIF-2␣), and to assess the role of HIF-1 and HIF-2 in controlling cited2 and vascular endothelial growth factor (VEGF) expression.Methods. Rat cells were cultured under normoxic (21% O 2 ) or hypoxic (2% O 2 ) conditions, and expression and promoter activity of HIF-2 target genes were evaluated. Gain-or loss-of-function experiments were performed to investigate the contribution of HIF isoforms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 33 publications
4
71
0
Order By: Relevance
“…Furthermore, our study shows that in contrast to HIF-1␣, CCN2 is a positive regulator of HIF-2␣ expression. This is relevant, as we have previously reported that in nucleus pulposus, HIF-2␣ controls the expression of cited2, a p300 interacting protein (29). By competing with HIF-␣ for p300 binding, cited2 suppresses transcriptional activity of HIF (29).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, our study shows that in contrast to HIF-1␣, CCN2 is a positive regulator of HIF-2␣ expression. This is relevant, as we have previously reported that in nucleus pulposus, HIF-2␣ controls the expression of cited2, a p300 interacting protein (29). By competing with HIF-␣ for p300 binding, cited2 suppresses transcriptional activity of HIF (29).…”
Section: Discussionmentioning
confidence: 86%
“…This is relevant, as we have previously reported that in nucleus pulposus, HIF-2␣ controls the expression of cited2, a p300 interacting protein (29). By competing with HIF-␣ for p300 binding, cited2 suppresses transcriptional activity of HIF (29). Thus, it is possible that through induction of the HIF-2␣-cited2 circuit, CCN2 may decrease HIF-1␣ activity and target gene expression.…”
Section: Discussionmentioning
confidence: 90%
“…[2][3][4][5] NP cells adapt to this hypoxic niche by modulating a key transcription factor, HIF1A (hypoxia inducible factor 1 a subunit), to promote cell survival, matrix synthesis, and to regulate glycolytic metabolism. [6][7][8][9][10][11][12][13] A recent study using NP-specific conditional Hif1a knockout mice also shows that HIF1A is required for postnatal NP cell survival in vivo. 14 Autophagy is a highly conserved cellular process where organelles and cytosolic proteins are encapsulated within target of rapamycin [serine/threonine kinase]) resulting in increased autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…However, only HIF1b was found in rat AF cells in vivo (93). In a hypoxic microenvironment, the a-subunits of HIF are stable and dimerize with the other subunits to bind hypoxia response elements (HREs) and promote the expression of protective mRNAs and proteins, such as vascular endothelial growth factor (VEGF), cited2 and galectin-3 to inhibit apoptosis (94)(95)(96). With regard to the ECM, HIF-1 was reported to promote the synthesis of aggrecan, which is the major proteoglycan expressed in discs (97).…”
Section: Hypoxic Stressmentioning
confidence: 99%